TRANSFORMASI PEMBELAJARAN JARING-JARING MAKANAN: STUDI IMPLEMENTASI MULTIMEDIA INTERAKTIF BERBANTUAN CANVA DI JENJANG SEKOLAH DASAR - Lilis Tasmayanti; L.R. Retno Susanti; Erna Retna Safitri (Postgraduate, University of Mataram, 2025)
The background of this research is based on the importance of using digital learning media that is engaging, interactive, and appropriate to the characteristics of 21st-century students to improve the effectiveness of the science learning process. The learning process is a stage of positive behavioral change in students, encompassing cognitive, affective, and psychomotor aspects that are oriented towards progress. This study aims to produce interactive learning multimedia using Canva on food web material in elementary schools that is valid, practical, and effective. The presence of learning media is the key to the success of the learning process in the classroom.The study used the Research and Development (R&D) method with the ADDIE model which includes five stages: Analyze, Design, Develop, Implement, and Evaluate. Data collection techniques included observation, interviews, questionnaires, and tests. The validation results showed that the media was considered very valid by material experts (92%), media (86%), and language (93.33%). Practicality tests through one-to-one and small groups produced an average of 93.72% with a very practical category. The effectiveness of the media is shown by the N-Gain value of 0.90 which is included in the high category. Thus, this learning multimedia is proven to be valid, practical, and effective for use in learning in elementary schools.